Multi-octave spanning, Watt-level ultrafast mid-infrared source - Butler, T. P.; Lilienfein, N.; Xu, J.; Nagl, Nathalie; Hofer, Christina; Gerz, D.; Mak, K. F.; Gaida, Christian; Heuermann, T.; Gebhardt, M.; Limpert, Jens; Krausz, Ferenc; et al. (JPhys Photonics, 2019)
We present a source of brilliant mid-infrared radiation, seamlessly covering the wavelength range between 1.33 and 18 μm (7500–555 cm−1) with three channels, employing broadband nonlinear conversion processes driven by the output of a thulium-fiber laser system. The high-average-power femtosecond frontend delivers a 50 MHz train of 250 fs pulses spectrally centered at 1.96 μm. The three parallel channels employ soliton self-compression in a fused-silica fiber, supercontinuum generation in a ZBLAN fiber, and difference-frequency generation in GaSe driven by soliton self-compressed pulses. The total output enables spectral coverage from 1.33 to 2.4 μm, from 2.4 to 5.2 μm, and from 5.2 to 18 μm with 4.5 W, 0.22 W and 0.5 W, respectively. This spatially coherent source with a footprint of less than 4 m2 exceeds the brilliance of 3rd-generation synchrotrons by more than three orders of magnitude over 90% of the bandwidth.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Intra-pulse difference frequency generation (DFG); Mid-infrared generation; Nonlinear optics; Supercontinuum generation; Ultrafast optics; ZBLAN optical fibre